MENGATASI KESULITAN BELAJAR MELALUI METODE DRILL (Penelitian Tindakan di Kelas Rendah SDI Al-Hakim Boyolangu Tulungagung) - Ayok Ariyanto (Universitas Muhammadiyah Ponorogo, 2016)
teaching learning activity is a purposeful thing created to bring the students to success. However, in the middle of this process, it often encounter obstacles. In this case, the problem was on the lack of the students understanding towards the lesson taught by the teacher. The research object were the students of class I Al-Hakim Islamic elementary school of Boyolangu. The data collection technique was through test, observation, interview, and fieldnotes. The collected data related to the drilling method application were analyzed qualitatively. From this research, it was found that: (1) the application of learning by using drilling method could improve the students learning achievement. (2) the students activeness in joining the learning process was increasing, it can be seen from the observation to the students activities, that there were improvement from the 1st cycle to the 2nd cycle, that was 60.71% improved to 82.69%. For the test results also increased from the students’ average 79.44 to 93.88. Likewise, in terms of completeness also had risen from 83.3% to 100%. Then it can be concluded that the application of drilling method can overcome mathematics learning difficulties of low-grade students.